De Marshall McLuhan à Harold Innis ou du village global à l’empire mondial - Gaëtan Tremblay (Tic & Société)
The author presents a personal reading of the contribution of two pioneering Canadians to communication studies, Marshall McLuhan and Harold A. Innis, the former still considered by many as information and communication technologies guru, the latter too often ignored by most researchers. Running counter the general trend stressing their affiliations, he highlights their differences. Rejecting their technological determinist standpoint, he proposes a comprehensive and critical summary of their analytical frameworks and methodologies, seeking to assess the influence of one and the other on his own perspective, and tracing their contribution to advancing, or stalling, the evolution of communication research. The author condenses his viewpoint in the title : we should go back from McLuhan to Innis, from a framework inspired by the global village metaphor to the one calling for the expansion of empires.